Opposite roles of bradykinin B1 and B2 receptors during cerebral ischaemia–reperfusion injury in experimental diabetic rats. (January 2016) - Sang, Hongfei; Liu, Ling; Wang, Liumin; Qiu, Zhongming; Li, Min; Yu, Linjie; Zhang, Hao; Shi, Ruifeng; Yu, Shuhong; Guo, Ruibing; Ye, Ruidong; Liu, Xinfeng; et al.
Abstract: Bradykinin receptors play important roles in cerebral ischaemia–reperfusion (I/R) injury of non‐diabetics. Their functions in diabetics, however, have not been studied. In this study, we hypothesized that bradykinin 1 receptor (B1R) and bradykinin 2 receptor (B2R) would be upregulated and participate in the regulation of diabetic ischaemic stroke. To investigate this, we first evaluated B1R and B2R expression at different time points after I/R in non‐diabetic and diabetic rats (Sprague–Dawley) by using real‐time quantitative reverse transcription polymerase chain reaction, western blotting, and immunofluorescence. Then, pharmacological inhibitors were separately administered via the tail vein to analyse their effects on cerebral ischaemia in diabetics. Both receptors were significantly upregulated after cerebral I/R in non‐diabetic and diabetic rats. B1R expression in diabetic rats increased in a sharper manner than in non‐diabetic rats, whereas B2R expression increased to the same level during the early stage of reperfusion but later became lower. Interestingly, the upregulated B1R was expressed in astrocytes, whereas B2R was mainly located in neurons in the ischaemic penumbra. Functional studies showed that inhibition of B1R significantly reduced infarct volume, neurological deficits, cell apoptosis, and neuron degeneration, probably by attenuating blood–brain barrier (BBB) disruption and post‐ischaemic inflammation, at 24 h after reperfusion. In contrast, B2R antagonist had opposite effects, and exacerbated BBB penetrability and tissue inflammation. These findings suggest that B1R and B2R have detrimental and beneficial effects, respectively in diabetic cerebral ischaemia, which might open new avenues for the treatment of ischaemic stroke in diabetic patients through selective pharmacological blockade or activation. Abstract : Diabetic rats were accompanied with more notable B1 receptor upregulation but less B2 receptor expression than their non‐diabetic counterparts after cerebral ischemia/reperfusion. B1 receptor and B2 receptor also involved in the regulation of ischemic brain injury in diabetic rats, the former detrimental but the latter beneficial.